The big picture: Mary Dallman, a role model - Marian Joëls (Stress, 2023)
Mary Dallman has left a legacy in neuroendocrinology, not only as the scientist who elaborated on new concepts such as rapid corticosteroid feedback pathways, but also as a role model, particularly for women who followed in her footsteps. In this contribution, I compare (i) the remarkable journey she made toward her position as the first female faculty member ever at the physiology department at USCF with that of generations after her; (ii) the contribution of our labs on rapid corticosteroid actions; and, (iii) finally, our experiences with unexpected findings for which one should always keep an open mind, a standpoint that was fervently advocated by Mary Dallman.